CANNING OF OIL SARDINE (SARDINELLA LONGICEPS)-NATURAL PACK - UNNIKRISHNAN NAIR, T S; MADHAVAN, P; BALACHANDRAN, K K; PRABHU, P V (Fishery Technology, 2017)
A simple and economic process for canning of oil sardine( Sardinella longiceps) in its own juice having very good organolepticcharacteristics has been developed. The process consistsin dipping eviscerated, scaled and cleaned fish in brine containingpotash alum and citric acid, packing in cans, exhaustingand seaming without addition of any filling medium and heatprocessing.Â